INTEGRASI HIDRO, ANGIN, SURYA, DAN PENYIMPANAN ENERGI DALAM SISTEM KELISTRIKAN RENDAH KARBON: TINJAUAN KOMPREHENSIF ATAS FLEKSIBILITAS, OPTIMASI OPERASI, DESAIN TEKNO-EKONOMI, DAN ARAH RISET TERKINI - Aswin; Lanto Mohamad Kamil Amali; Burhan Liputo (Program Vokasi-Universitas Negeri Gorontalo, 2026)
The transition to a low-carbon electricity system is driving the strategic role of hydropower, both as a manageable renewable generator and as the backbone of system flexibility to accommodate the intermittency of wind and solar energy. In recent years, the evolution of studies is no longer limited to conventional reservoir operations but has expanded to hybrid hydro–wind–photovoltaic systems, pumped hydro energy storage (PHES), hydro–PV–storage, hydro–hydrogen, and multi-energy configurations integrating compressed air energy storage (CAES) and liquid air energy storage (LAES). This review article synthesizes the literature to map recent developments on four main themes: (1) the role of hydropower flexibility in the integration of variable renewable energy (VRE), (2) modeling and optimization of multi-scale operations, (3) capacity design and techno-economic evaluation of storage technologies, and (4) issues of reliability, safety, ecology, and artificial intelligence (AI) for prediction and control. Recent literature indicates that coordinating hydro with wind, solar, and storage can increase renewable energy utilization, reduce curtailment, improve operational stability, and enhance economic benefits, particularly when operating models incorporate spatio-temporal correlations, hydraulic constraints, market mechanisms, and flexibility requirements. Gaps remain in multi-scale integration, the incorporation of ecological indicators into market optimization, standardization of economic evaluations, and field validation of intelligent control strategies.